The Role of Islamic Communication in Character Formation of the Young Generation: A Literature Analysis of Moral and Educational Messages - Fajar Kurniadi (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This article examines the multifaceted role of Islamic communication in shaping the character of the younger generation, focusing on the transmission of moral and educational messages. In an era marked by rapid technological advancements, globalization, and evolving societal values, the influence of Islamic communication is more critical than ever. This analysis delves into the various channels and methods employed in conveying Islamic teachings, the challenges faced, and the potential impact on the character development of young Muslims. It explores the interplay between traditional and modern forms of communication, the role of religious leaders and educators, and the influence of digital platforms and social media. The study aims to provide insights into how Islamic communication contributes to fostering positive values, ethical conduct, and a strong sense of identity among the youth, while also addressing the complexities of navigating contemporary challenges.